Slope position- mediated soil environmental filtering drives plant community assembly processes in hilly shrublands of Guilin, China - Chen, Kunquan; Pan, Yuanfang; Li, Yeqi; Cheng, Jiaying; Lin, Haili; Zhuo, Wenhua; He, Yan; Fang, Yaocheng; Jiang, Yong (Frontiers in Plant Science, 2023)
Background and aims: Understanding how topography and environmental factors drive plant community assembly is a major goal of community ecology. Analysis of community-weighted mean (CWM) plant traits can distinguish assembly processes. Methods: We surveyed woody shrub plant communities in 108 10 m x 10 m plots from three slope positions (foot, middle, and upper) in a low hilly area of Guilin, China and measured the CWMs of four plant functional traits—specific leaf area (SLA), leaf dry matter content (LDMC), leaf chlorophyll content (LCC), and leaf thickness (LT)—along with nine abiotic environmental factors, including soil water content (SWC), soil pH, and multiple other soil nutrient factors. We used ANOVA and Tukey HSD multiple comparisons to assess differences in functional trait CWMs and environmental factors across the three slope positions. We further used redundancy analysis (RDA) to test relationships between trait CWMs and environmental factors and quantified the strength of environmental filtering on trait CWMs with a three-step trait-based null model approach. Results :The CWMs of three leaf functional traits and all soil environmental factors except soil pH showed significant differences across the three slope positions. Soil available nitrogen (AN), total nitrogen (TN), available potassium (AK), and soil organic matter (SOM) were positively correlated with the CWM SLA and LCC along the first RDA axis and soil total potassium (TK), total phosphorous (TP), and SWC were positively correlated with the CWM LDMC along the second RDA axis. Environmental filtering was detected for the CWM SLA, LDMC, and LCC but not LT at all three slope positions. Conclusions: Soil nutrients vary along slope gradients and can cause variability in plant functional traits in shrub communities. Detecting habitat filtering can depend on traits considered, as not all traits are filtered by specific environments.